Plasmonic tunnel junctions for single-molecule redox chemistry - Bart de Nijs (Nature Portfolio, 2017)
Plasmons in sub-nm cavities can enable chemical processes within plasmonic hotspots. Here the authors use surface-enhanced Raman spectroscopy to track hot-electron-induced chemical reduction processes in aromatic molecules, thus enabling observation of redox processes at the single-molecule level.